A moral argument for frozen human embryo adoption. (26th November 2019) - Lovering, Rob
Abstract: Some people (e.g., Drs. Paul and Susan Lim) and, with them, organizations (e.g., the National Embryo Donation Center) believe that, morally speaking, the death of a frozen human embryo is a very bad thing. With such people and organizations in mind, the question to be addressed here is as follows: if one believes that the death of a frozen embryo is a very bad thing, ought, morally speaking, one prevent the death of at least one frozen embryo via embryo adoption? By way of a three‐premise argument, one of which is a moral principle first introduced by Peter Singer, my answer to this question is: at least some of those who believe this ought to. (Just who the "some" are is identified in the paper.) If this is correct, then, for said people, preventing the death of a frozen embryo via embryo adoption is not a morally neutral matter; it is, instead, a morally laden one. Specifically, their intentional refusal to prevent the death of a frozen embryo via embryo adoption is, at a minimum, morally criticizable and, arguably, morally forbidden. Either way, it is, to one extent or another, a moral failing.